Erosion of cold sprayed aeronautical coatings*. (2nd September 2019) - Cruz, D.; Garrido, M. A.; Múnez, C. J.; Rico, A.; Poza, P.
ABSTRACT: Aluminium-Silicon alloys, like Al C355, are extensively used in aeronautical applications, where light materials are required. Consequently, it is necessary to develop maintenance and overhaul technologies to extend the life of metallic components used in the aeronautical sector. Cold Spray (CS) represents a promising alternative to repair damaged light alloys surfaces. However, the repaired component should exhibit similar properties as the original substrate. In particular, degradation by erosion is usual during service in aeroplane operation. This is precisely the aim of this research: to evaluate the erosion performance of Al C355 coatings cold sprayed onto the same bulk alloy. Air jet-erosion tests were performed on the coatings and substrate, according to ASTM G76 standard. Coatings processed by CS using standard parameters exhibit lower erosion performance than the substrate. However, the erosion resistance of coatings deposited using improved conditions was similar to that observed in the uncoated substrate.